Penerapan Model Cooperative Learning Berbantuan Media Interaktif untuk Meningkatkan Kemampuan Kerjasama Siswa Kelas IV - Rama Rama; Nurdinah Hanifah; Rana Gustian Nugraha (Journal on Education, 2024)
The research began by reviewing the results of interviews conducted with 4th grade educators at SDN 019 Pabaki, Bandung City and referring to the findings of observations and pretests conducted in class. The findings show that students' collaboration capacity and academic achievement are still at a low level. The aim of this research is to explain the use of cooperative learning models assisted by interactive media to improve student collaboration skills and academic achievement. The research methodology used in this research is classroom action research using the spiral model developed by Kemis and Taggart, which includes several cycles. The process consists of four stages: planning, implementation, observation, and reflection. This research involved 29 students. The research instrument consists of an observation sheet to assess students' collaboration skills, an observation sheet to evaluate the implementation of the cooperative learning model using interactive media, and a test sheet. Research findings show that the implementation of a cooperative model supported by interactive media results in a significant increase in students' collaboration skills. In cycle 1 there was an increase of 71.50% and in cycle 2 there was an increase of 81%. Before the intervention, collaboration ability was at the pre-cycle level of 37.42%. Apart from that, it is known that the percentage of completeness of student learning outcomes increased from 39.70% in the pre-cycle to 79.30% in cycle 1 and reached 100% in cycle 2.